Growth of ZnO Thin Films on Polar Oxide Surfaces By Atomic Layer Deposition - (:unkn) unknown (My University, 2013)
Polar heterointerfaces of MgO(111) and the II-VI semiconductor ZnO are of technological interest for transparent conducting electrode applications. Growth and structure of thin films on polar surfaces can be different than on non-polar surfaces due to the large surface energy of polar surfaces. We have grown ZnO on unreconstructed MgO(111)-(1x1)-OH terminated and reconstructed MgO(111)-(√3x√3)R30° polar oxide surfaces using atomic layer deposition. A homemade UHV-interfaced viscous-flow atomic layer deposition (ALD) reactor with in-situ quartz crystal monitor was used to grow ZnO thin films on the MgO(111) substrates. Surface morphology studies revealed that the surface roughness increases with ZnO film thickness and that reconstructed MgO(111) is a better substrate for production of smooth ZnO films. Thin-film structural analysis revealed that ZnO thin films are polycrystalline, having the wurtzite structure, with preferential growth along the c-axis. ZnO grown on MgO(111)-(√3x√3)R30° substrates show strong preferential growth along the polar (002) direction. In contrast, growth along the non-polar (100) and (101) directions is also observed when grown on MgO(111)-(1x1) substrates. These observations indicate the crystal orientation during ALD ZnO growth depends not only on temperature but also on the surface terminations and symmetry of the substrates. We also investigated the growth of ALD ZnO on polar 6H-SiC(0001) substrates and non-polar MgO(100), α-Al2O3(0001) and oxidized Si(100). Our study revealed that, for non-polar substrates, ALD ZnO grows along the non-polar (100) and (101) directions along with the polar (002) direction. Highly c-axis-oriented ALD ZnO thin film growth on 6H-SiC(0001) indicates that lattice matched substrates favor growth of high-quality ALD ZnO. Finally, we investigated ZnO thin film growth on unreconstructed MgO(111)-(1x1)-OH terminated and reconstructed MgO(111)-(√3x√3)R30° polar oxide surfaces using pulsed-laser deposition (PLD). Structural studies revealed that surface termination affects the PLD ZnO growth similar to the way it affected ALD ZnO growth.
Keywords: Atomic Layer Deposition; Polar Oxide; Reconstructed Surfaces; Thin Films; Viscous-Flow ALD Reactor; ZnO